Sexual Acquisition and Transmission of HIV Cooperative Agreement Program (SATHCAP), 2006-2008 (United States) Restricted Use Files - Iguchi, Martin Y. ([Verlag nicht ermittelbar], 2010)
The Sexual Acquisition and Transmission of HIV Cooperative Agreement Program (SATHCAP) is a multisite study which was founded by the National Institute on Drug Abuse (NIDA) and was designed to assess the role of drug use in the sexual transmission of the human immunodeficiency virus (HIV) from traditional high-risk groups, such as men who have sex with men (MSM) and drug users (DU), to lower risk groups, such as non-drug-using sexual partners. The study was conducted in three United States cities: Los Angeles, CA; Chicago, IL; Raleigh-Durham, NC; and in St. Petersburg, Russia. NIDA brought together researchers from the University of California-Los Angeles; the University of Chicago-Illinois; Research Triangle Institute International in Raleigh-Durham, NC; Yale University, with the Biomedical Center (Yale/BMC) in St. Petersburg, Russia; and the RAND Corporation. SATHCAP conducted a cross-sectional study across the four sites using a respondent-driven sampling (RDS) sampling approach, a common questionnaire, and similar biological testing. The goal of sampling approach was to recruit an RDS sample of MSM, DU, and individuals who were both MSM and DU (MSM/DU), as well as a sample of sex partners of MSM, DU, and MSM/DU, and sex partners of sex partners. The key research questions for SATHCAP were: (1) To what extent do HIV infections among DU and MSM populations spread to uninfected non-DU and non-MSM individuals through sexual activity? (2) What is the role of drugs in this spread? (3) What individual, behavioral, network, and structural characteristics determine the speed, extent, and path of this spread? Respondents were asked questions about their sexual relationships with their partners, method of drug use, name of drugs they used, method of sharing drugs, and method of sexual activities with their partners.